Jürgen Habermas’s postconventional constractarianism as cosmopolitan constitutionalism - Cern, Karolina M. (Lingua Posnaniensis, 2017)
In the course of this paper article I shall depict in what way Jürgen Habermas’s application of the discourse theory to the democratic polity transforms the contractarian theoretical framework, presuming, however, that the reader is familiar with the general theoretical framework and the basic concepts characteristic for this political tradition. Moreover, I will also show that the relevance of this transformation consists in delivering a justification of a kind of cosmopolitan constitutionalism.